LncRNA H19 contributes to Rh2-mediated MC3T3-E1cell proliferation by regulation of osteopontin - Dong, B.; Pang, T.-T. (Cellular and Molecular Biology, 2017)
20(R)-ginsenoside Rh2 (Rh2) is one of the most active components of red ginseng, possessing the beneficial effects in cancer prevention and metabolic diseases. However, the detailed mechanisms that contribute to Rh2-mediated bone formation remain largely unknown. In this study, we assessed the expression of 17 long non-coding RNAs (lncRNAs) in cultured MC3T3-E1 cells under Rh2 treatments. We found that lncRNA H19 was significantly increased in Rh2-treated MC3T3-E1 cells. Expression of lncRNA H19 was promoted in a dose- and time-dependent manner after Rh2 treatments. Increased expression of lncRNA H19 resulted in osteopontin (OPN) overexpression in Rh2-treated MC3T3-E1 cells. Furthermore, knockdown of lncRNA H19 by specific siRNAs significantly abolished the Rh2-mediated cell proliferation effects. Knockdown of lncRNA H19 also decreased both mRNA and protein levels of OPN in the Rh2-treated cells, which was accomplished by inhibiting histones H3 and H4 acetylation of OPN promoter. Importantly, OPN knockdown fully blocked Rh2 induced MC3T3-E1 cell proliferation. Our results suggest that lncRNA H19 is an important contributor to Rh2-mediated MC3T3-E1 proliferation by regulation of OPN.